Study on the Path of Enabling High-quality Agricultural Development in Anhui Province with New Quality Productivity - Wang, Zihuan; Zhou, Tao (International Journal of Social Sciences and Public Administration, 2024)
With the continuous progress of science, technology and society, new quality productivity is gradually becoming a strong support and internal driving force for high-quality development of agriculture, which is of great significance for transforming traditional agriculture and promoting agriculture to intelligent, low-carbon and modern transformation. With its "new" and "quality" as the fundamental, new quality productivity has the characteristics of high-tech, high efficiency, high quality, etc., and has a strong leading role in the all-round transformation of traditional agriculture. On the basis of reviewing the literature related to the new quality productivity and the agricultural development of Anhui province, this paper first put forward the author’s interpretation of the connotation of new quality productivity, and then analyzed the conditions of Anhui province’s transformation from a large agricultural province to a strong agricultural province. On this basis, it explored the path of enabling the high-quality agricultural development of Anhui province by new quality productivity. Finally, it is concluded that in order to achieve this goal, we must strictly implement the new development concept and promote the transformation of traditional agriculture to the direction of wisdom, ecology and industrialization.